2021
DOI: 10.1111/bcp.15012
|View full text |Cite
|
Sign up to set email alerts
|

Methodological issues in research on drug‐related admissions: A meta‐epidemiological review with focus on causality assessments

Abstract: Aim: To investigate methodological aspects potentially related to the diverging scientific literature on the prevalence of drug-related hospitalisations, focusing on causality assessments.Methods: Original studies contributing data to a recent meta-analysis were reviewed.Methodological aspects, in particular those related to causality assessments, were extracted and compiled.Results: Thirteen studies provided data on the prevalence of drug-related admissions.Seven studies focused on adverse drug reactions (pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(19 citation statements)
references
References 32 publications
0
19
0
Order By: Relevance
“…However, at the same time, safer alternatives are being used in clinical practice, high-risk medications are being withdrawn from the market, and preventative measures are being implemented in clinical practice. The prevalence of DRAs differs due to inconsistencies in the definitions and methods of DRA identification ( Leendertse et al, 2010 ; Linkens et al, 2020 ; Laatikainen et al, 2021 ), the selected threshold of causality assessment ( Wallerstedt et al, 2021 ), patient population ( Beijer and de Blaey, 2002 ; Leendertse et al, 2010 ; Laatikainen et al, 2021 ) and whether the denominator includes all admissions, only acute admissions, or specific wards ( Leendertse et al, 2010 ). When comparing the prevalence of DRAs, one has to take all these things into account.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, at the same time, safer alternatives are being used in clinical practice, high-risk medications are being withdrawn from the market, and preventative measures are being implemented in clinical practice. The prevalence of DRAs differs due to inconsistencies in the definitions and methods of DRA identification ( Leendertse et al, 2010 ; Linkens et al, 2020 ; Laatikainen et al, 2021 ), the selected threshold of causality assessment ( Wallerstedt et al, 2021 ), patient population ( Beijer and de Blaey, 2002 ; Leendertse et al, 2010 ; Laatikainen et al, 2021 ) and whether the denominator includes all admissions, only acute admissions, or specific wards ( Leendertse et al, 2010 ). When comparing the prevalence of DRAs, one has to take all these things into account.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, it was suggested that the widespread use of a signal detection cut-off in descriptive prevalence studies may have contributed to the perception that harmful drug treatment is the major problem of health care ( Wallerstedt et al, 2021 ). Therefore, it should be underlined that medications often pose a risk in certain situations and many ADEs are multifactorial in nature.…”
Section: Discussionmentioning
confidence: 99%
“…It does not require a clinical expert panel, which previous studies on drug-related hospital visits have had to rely on. Wallerstedt et al have raised common methodological issues in research on DRAs and provided suggestions for future research [11]. In line with these suggestions, we need to adress that AT-HARM10 only distinguishes between visits that are unlikely to be and those that are possibly drug-related.…”
Section: Strengths and Weaknessesmentioning
confidence: 95%
“…Two recent systematic reviews on drug-related hospital admissions (DRAs) report an average prevalence of 15% and 21% of which at least a third seems preventable [3,9]. DRAs are therefore an important outcome in research areas with a strong link to pharmacotherapy, such as clinical pharmacy [10,11]. However, great heterogeneity in methods to measure DRAs exist and validated methods are lacking [3,11].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation